Optimization of Catalyst Structure for Asymmetric Propargylation of Aldehydes with Allenyltrichlorosilane. Issue 23 (16th October 2020) - Vaganov, Vladimir Yu.; Fukazawa, Yasuaki; Kondratyev, Nikolay S.; Shipilovskikh, Sergei A.; Wheeler, Steven E.; Rubtsov, Aleksandr E.; Malkov, Andrei V.
Abstract: The design of catalysts for asymmetric propargylations remains a challenging task, with only a handful of methods providing access to enantioenriched homopropargylic alcohols. In this work, guided by previously reported computational predictions, a set of atropisomeric bipyridine N, N' ‐dioxides was tested as Lewis base catalysts for the asymmetric propargylation of aldehydes with trichloroallenylsilane. The catalysts are easily prepared in four simple steps starting from readily available methyl ketones. Aryl‐substituted derivatives proved to be highly active and showed a high level of enantiocontrol even at 1 mol% loading. The reaction scope includes a wide range of aromatic, heteroaromatic, and unsaturated aldehydes. New computations confirm that the key stereodetermining transition state structures for the synthesized catalysts are similar to those previously reported for the model structure. Abstract :